Insecticidal activities of constituents of Litsea cubeba fruit extracts effective against the maize weevil (Coleoptera: Curculionidae). Issue 5 (11th October 2017) - Zhang, Hong Jian; Zheng, Lian He; Zhao, Kuo; Chen, Yan; Yi, Zou
Abstract: In this study, we investigated the insecticidal activities, including contact toxicity, fumigant toxicity, and repellent activity, of Litsea cubeba fruit extracts against Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae). The extracts, obtained by liquid–liquid extraction in n -hexane, ethyl acetate, chloroform, and water were analyzed by gas chromatography–mass spectrometry. Among the different extract types, chloroform extracts exhibited the strongest repellent, contact, and fumigant activities against S. zeamais . The main components of the chloroform extracts were identified as laurine (21.15%) and 2, 6-diisopropyl aniline (16.14%), followed by chlorobutanol (10.54%), 3- O -methyl- N -acetyl-d -glucosamine (10.03%), and 6-methyl-5-hepten-2-one (8.33%). Among the identified components of the chloroform extracts, chlorobutanol showed the strongest fumigant toxicity (LD50 = 21.91 mg/liter), contact toxicity (LD50 = 54.25 µg/adult), and repellent activity against S. zeamais . These results indicate that L. cubeba fruit extracts possess natural insecticide-like activities against S. zeamais .